Characterization and fabrication of InGaN/GaN MQWs and LEDs on macroporous Si substrate - Dang, Dominic Thor Weng (2011)
Growth of indium gallium nitrite (InGaN)/gallium nitride (GaN) multiple quantum well (MQW) on porous silicon (Si) and porous GaN on sapphire had been studied. Electrochemical etching was carried out to produce the porous surfaces. Effects of current, temperature, illumination and durations on electrochemical etching were investigated.